Voter Verification Using Rubik's Cube - Moayed, Majid Javid (2009)
Electronic voting systems such as Direct Recording Electronic systems have become more prominent in election processes because of their potential in consistency of implementing security policies. Despite of this potential, most of the systems still exclusively rely on the integrity of election officers and poll workers to ensure that the election maintains the proper security and privacy. Various cryptography voting schemes have been proposed to tackle the problem of how to trust the voting machine with correct recording of votes. However, still the probability of cheating is relatively high. This thesis proposes an electronic voting system that provides a trustable voter verification system by scrambling ballots as the cryptography method. The system selects and unselects candidates, and Rubik’s cube is used for encrypting ballots and generating receipts. The receipts can be used by voters to verify their votes in the final tally of votes. Cheating probabilities were analyzed to evaluate the strength of the proposed system. The results of the probability analysis show that cheating probabilities in the proposed system are very low.